1996
DOI: 10.1080/02652039609374464
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium levels in Italian diets and in selected foods from aluminium utensils

Abstract: In Italy, data on aluminium concentration in food items are scarce although aluminium containers are widely used to cook, to freeze or to wrap foods (foil) and it is known that aluminium can migrate from containers to foods. Therefore, an experimental study was carried out to quantify aluminium exposure from ingestion of actual total diets and from migration from containers to foods in conditions representative of the actual use. Samples of 24 h diets were collected, homogenized, lyophilized and the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 2 publications
5
26
0
3
Order By: Relevance
“…Four separate liver enzymes, including AST and ALT, which, together, are known as transaminases, ALP, which is a cholestatic liver enzyme, and LDH, are reliable indicators of liver function. AST and ALT are critical enzymes for biological processes [25] . An increase in serum AST and ALT in rats treated with AlCl 3 was in agreement with previous findings demonstrating that AlCl 3 exposure promoted liver necrosis[ 39,41,42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four separate liver enzymes, including AST and ALT, which, together, are known as transaminases, ALP, which is a cholestatic liver enzyme, and LDH, are reliable indicators of liver function. AST and ALT are critical enzymes for biological processes [25] . An increase in serum AST and ALT in rats treated with AlCl 3 was in agreement with previous findings demonstrating that AlCl 3 exposure promoted liver necrosis[ 39,41,42] .…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, the FAO/WHO Expert Committee on Food Additives reported that the daily intake of aluminum in children was between 2 and 6 mg, and in adults, it varied between 6 and14 mg [25][26][27] . Therefore, the daily intake of aluminum in an adult with a mean body weight 70 kg is between 0.1 and 0.2 mg kg −1 body weight.…”
Section: Determination Of Alcl 3 Daily Dosementioning
confidence: 99%
“…In 1989, the FAO/WHO Expert Committee on Food Additives reported that the daily intake of aluminum in children ranged between 2 and 6 mg and in adults, it varied between 6 and 14 mg [34][35][36] . Therefore, the daily intake of aluminum in an adult with a mean body weight 70 kg ranges between 0.1 mg and 0.2 mg kg −1 body weight.…”
Section: Dose Determinationmentioning
confidence: 99%
“…It is well established that several components in orange juice migrate into polymers [24]. Aluminium surfaces can deteriorate whenever they come into contact with salty, acidic, or even neutral aqueous media [25]. Because of those corrosive effects, Al can migrate to the fruit juice and its content may be elevated in the products.…”
Section: Discussionmentioning
confidence: 99%